The Influence of Learning Motivation on Mathematics Learning Achievement in terms of Gender of Class VIII Students of SMP Negeri 5 Tarakan - Shinta Wulandari; Hermansyah Hermansyah; Yanti Indah Pratiwi (Journal of Education and Learning Mathematics Research (JELMaR), 2021)
This study aims to determine the effect of learning motivation on mathematics learning achievement of class VIII students of SMP Negeri 5 Tarakan, the effect of gender on mathematics learning achievement of class VIII students of SMP Negeri 5 Tarakan, and the effect of interaction between learning motivation and gender on mathematics learning achievement. VIII grade students of SMP Negeri 5 Tarakan. The type of research used is quantitative with a causal associative approach. The population in this study were all eighth grade students of SMP Negeri 5 Tarakan. Sampling was carried out using Proportionate Stratified Random Sampling. The sample in this study amounted to 163 students, including 88 male students and 75 female students. Data was collected using a questionnaire and score documentation. Data analysis technique used descriptive analysis and inferential analysis which was processed with the help of SPSS 24 application. Descriptive analysis used mode, while inferential analysis used Two Way ANOVA. Based on the results of the analysis with a significance level of 5% or 0,05, it can be concluded that: (1) there is an influence of learning motivation on mathematics learning achievement of class VIII students of SMP Negeri 5 Tarakan; (2) there is an influence of gender on the mathematics learning achievement of eighth grade students of SMP Negeri 5 Tarakan; (3) there is no interaction effect between learning motivation and gender on mathematics learning achievement of class VIII students of SMP Negeri 5 Tarakan.